TINGKAT PENERAPAN TEKNOLOGI PENGELOLAAN TANAMAN TERPADU (PTT) PADA USAHATANI PADI SAWAH DI KECAMATAN BIBOKI MOENLEU KABUPATEN TTU - Joka, Umbu; Abani, Maria Anita; Nubatonis, Agustinus; Mambur, Yohanes P. V (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
Integrated Crop Management is a major technology component and an adaptive option that can be adapted to local agroecological conditions. This study aims to determine the level of application of Integrated Crop Management (ICM) technology and the obstacles faced by farmers in the application of ICM technology. This research was conducted in August - September 2020, which was located in Oepuah Utara Village, Biboki Moenleu District, North Central Timor Regency, while the method used to see the success rate of ICM technology application was using scoring. The results of the research on the level of application of ICM technology are; low with a percentage of 55%. There are still obstacles to be faced (a) The technical application of the jajar legowo plant system with the jajar legowo 2:1 and 4:1 technique has not been able to be implemented by farmers because many use the jajar legowo 8:1 and 10:1 technique. (b) planting seeds 1 to 3 per clump cannot be carried out optimally because there are still attacks by the golden snail, so farmers are still doing a lot of planting. (c) fertilizing should be 3 times per planting season, farmers cannot do it because they do not use basic fertilizers. (d). pest control using chemical drugs because farmers do not observe pests and clean by hand.